Penerapan Model Pembelajaran Discovery Learning Untuk Meningkatkan Hasil Belajar Siswa Pelajaran Fiqh: Application of Discovery Learning Model to Improve Student Learning Outcomes in Fiqh Lessons - Maimunah, Maimunah (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study aims to improve the learning outcomes of Jurisprudence subjects with the Discovery Learning Model for Class X-B students at MAN 3 Hulu Sungai Selatan in 2023, this type of research uses Classroom Action Research (PTK), consisting of four stages namely; planning, action, observation, reflection. The research subjects were Class X-B MAN 3 Hulu Sungai Selatan students totaling 21 students. Data collection methods used observation, documentation, tests and interviews. The results of this study showed an increase in students' critical and collaborative thinking significantly. The percentage of students' critical thinking in the pre-cycle was 48%, cycle I was 65%, cycle II meeting I rose to 85%, cycle III rose to 95%. Students' Learning Outcomes obtained in cycle I was 84.55%, but in cycle II it became 89.25%, cycle III the application of Discovery Learning was increased again so that the percentage obtained rose to 97.55%. The application of the Discovery Learning model can improve Learning Outcomes by making modifications in terms of; use of interesting media, seating arrangements, and effective classroom management strategies.